Occludin as a functional marker of vascular endothelial cells on tube‐forming activity. Issue 2 (17th August 2017) - Kanayasu‐Toyoda, Toshie; Ishii‐Watabe, Akiko; Kikuchi, Yutaka; Kitagawa, Hiroko; Suzuki, Hiroko; Tamura, Hiroomi; Tada, Minoru; Suzuki, Takuo; Mizuguchi, Hiroyuki; Yamaguchi, Teruhide
Abstract : Cell therapy using endothelial progenitor cells (EPCs) is a promising strategy for the treatment of ischemic diseases. Two types of EPCs have been identified: early EPCs and late EPCs. Late EPCs are able to form tube structure by themselves, and have a high proliferative ability. The functional marker(s) of late EPCs, which relate to their therapeutic potential, have not been fully elucidated. Here we compared the gene expression profiles of several human cord blood derived late EPC lines which exhibit different tube formation activity, and we observed that the expression of occludin (OCLN) in these lines correlated with the tube formation ability, suggesting that OCLN is a candidate functional marker of late EPCs. When OCLN was knocked down by transfecting siRNA, the tube formation on Matrigel, the S phase + G2 /M phase in the cell cycle, and the spheroid‐based sprouting of late EPCs were markedly reduced, suggesting the critical role of OCLN in tube formation, sprouting, and proliferation. These results indicated that OCLN plays a novel role in neovascularization and angiogenesis. Abstract : siRNA for OCLN inhibits tube formation of late EPC.